WhatsApp as a facilitator of expressions of gratitude for palliative care professionals. (October 2022) - Rodríguez, Marco; Feng, Ancu; Menjívar, Cecilia; López-Saca, Mario; Centeno, Carlos; Arantzamendi, Maria
Abstract: Introduction: Family members significantly value the professional and humane support that medical teams provide in the process of caring for patients with advanced diseases. Communication is currently changing, making it of interest to explore technology's possible influence on communication and on the care relationship. It remains unknown whether this can vary based on increased use of technology in patient care. Using communication technologies can facilitate recognition of professional support through the expression of gratitude aimed at healthcare professionals. The objective here is to describe expressions of gratitude sent via WhatsApp messages by patients who receive treatment from a palliative care team and their relatives. Method: A generic qualitative methodology was used. The palliative care service studied used WhatsApp in the patient/family-professional relationship. A content analysis of 130 WhatsApp messages sent to the professionals and containing expressions of gratitude was carried out. Two researchers inductively performed the analysis. Analysis included aspects for which senders were most grateful and others, such as who the messages came from, whether they were reactive or spontaneous and to whom they were directed. Results: Almost all of the patients treated transmitted their gratitude via WhatsApp. It was also observed that family members were most grateful for features of the care received (i.e., affection, availability), the professional's support (i.e., accompaniment, comfort) and the professional's qualities (i.e., professionalism, kindness). They also appreciated symptom control and attempts to resignify loss; these aspects received the most expressions of gratitude in the messages. In turn, all the messages contain expressions of support for palliative care professionals, evidencing a patient/family-professional relationship. Conclusion: The use of communication technologies like WhatsApp can contribute to the perception of professionals' availability and closeness and become a facilitator of expressions of gratitude that specify the aspects that family members most appreciate from the palliative care team, such as skills related to humane care and availability.